COMPARATIVE EDGES OF NOSTALGIA AND ARTISTIC LANGUAGE IN THE POETICS OF ARTISTIC THOUGHT - Tadjibaev Musazhan Sabirovich (International Journal of Literature and Language Studies, 2026)
Using examples from fiction, the article reveals the association of the concepts of space and time, which is an important category within the framework of the formation of artistic thinking.